A Soluble Ladder‐Conjugated Star‐Shaped Oligomer Composed of Four Perylene Diimide Branches and a Fluorene Core: Synthesis and Properties. Issue 32 (26th June 2014) - Zhang, Youdi; Chen, Lingcheng; Zhang, Kaichen; Wang, Helin; Xiao, Yi
Abstract A new ladder‐conjugated star‐shaped oligomer electron‐transporting material TetraPDI‐PF, with four perylene diimide (PDI) branches and a fluorene core, was efficiently synthesized. The oligomer is highly soluble in dichlorobenzene with a solubility of 155 mg mL−1, which is higher than those of PDI (35 mg mL−1) and PDI‐Phen (70 mg mL−1). Demonstrated by thermogravimetric analysis (TGA), the oligomer exhibits excellent thermal stability with the decomposition temperature (Td) of 291.2 °C, which is 65 °C higher than that of PDI. Cyclic voltammetry (CV) and differential pulse voltammetry (DPV) were employed to investigate the electrochemical properties. Although the CV curves of TetraPDI‐PF are successively scanned for 15 cycles, they still remain invariable reduction potentials. The oligomer also shows outstanding photostability, even better than PDI, which maintains 99 % fluorescence intensity after irradiation for 10 min using maximum laser intensity. In the steady‐state space‐charge‐limited current (SCLC) devices, TetraPDI‐PF exhibits higher intrinsic electron mobility of 2.22×10−5 cm2 V−1 s−1, three orders of magnitude over that of PDI (3.52×10−8 cm2 V−1 s−1). The bulk heterojunction (BHJ) organic solar cells (OSCs) using TetraPDI‐PF as non‐fullerene acceptors and P3HT as donors give optimum power conversion efficiency (PCE) of 0.64 %, which is 64 times that of the PDI:P3HT BHJ cells.